Jasmonic acid signaling pathway is involved in agaro-oligosaccharides-induced disease resistance of peach fruit through PpMYC2-activated transcription of PpPGIP1 - Li, Qian; Wei, Yingying; Jiang, Shu; Ye, Jianfen; Chen, Yi; Xu, Feng; Lou, Yongjiang; Ding, Phebe; Shao, Xingfeng (Elsevier B.V., 2025)
Agaro-oligosaccharides (AO) can enhance peach fruit resistance to Monilinia fructicola and reduce postharvest decay, but its molecular mechanism is unclear. In this study, transcriptome analysis and RT-qPCR analysis revealed that AO activated the expression of genes associated with jasmonic acid (JA) synthesis (PpLOX5–1/PpLOX5–2/PpAOC/PpAOS/PpOPR2) and signal transduction (PpMYC2/PpJAZ5), along with a rise in JA content. Additionally, AO significantly up-regulated the expression of the gene encoding polygalacturonase-inhibiting protein 1 (PpPGIP1) participating in plant-pathogen interaction. Yeast one-hybrid assay and electrophoretic mobility shift assay revealed that PpMYC2 bound to the PpPGIP1 promoter through the G-box element. Dual luciferase reporter assay in tobacco, as well as transient overexpression and silencing of PpMYC2 in peach fruit, demonstrated that PpMYC2 positively regulated PpPGIP1 expression. In summary, our findings indicated that AO activated JA synthesis and signal transduction, subsequently triggering PpMYC2 to positively regulate PpPGIP1 expression, thereby boosting the resistance of peach fruit to M. fructicola infection.